European defense sovereignty in the making: Notable gains, enduring dilemmas - Tuomas Iso-Markku; Niklas Helwig (EconPol Forum, 2025)
The combination of Russia's war against Ukraine and the declining US engagement in Europe have resulted in increased strategic convergence between Europeanist and Atlanticist states. For the time being, the primary goal is to strengthen NATO's "European pillar." To do so, member states will also use EU tools, which will help them to work toward the NATO spending goals. Key questions remain - especially how to balance national and collective defense efforts. The ReArm Europe plan, for example, increases national fiscal space, but does little to foster EU-level cooperation. At the same time, Europeans are still unsure to what extent they can, or want to, replace US capabilities. This is where the old dividing line between European states is still visible. Other trade-offs include rearming quickly versus long-term defense industrial investment, and closing current capability gaps versus focusing on future technologies.
Keywords: 330